(untitled) (Research, Society and Development, 2021)
In view of the current pandemic scenario caused by COVID-19, it can generate a significant cardiovascular involvement, which is the main risk factor for stroke. Thus, the present study aimed to describe the risks of stroke as a neurological complication in patients affected by COVID-19. The chosen methodology was a bibliographic review of the integrative literature review type. To carry out this study, the following databases were consulted: MEDLINE, Scholar Google, LILACS, SCIELO and Repositories. DeCS was used in an associated way: COVID-19; Brain stroke; Risk factors; Neurology and Coronavirus. Inclusion criteria were: articles available in full, available in Portuguese and English and published between 2019 and 2021. Exclusion criteria were: incomplete articles, letters to the editor, debates, reviews, abstracts or articles published in annals of events, unavailable in full and duplicates. After applying the criteria, 11 studies remained. It is known that COVID-19 is a single-stranded RNA virus named SARS-CoV-2, having an affinity for the respiratory system. However, published studies report that COVID-19 is also able to attack the Central Nervous System, which can cause other diseases, such as stroke, which can occur through a rupture of a blood vessel located in the brain, or by occlusion of the brain. blood flow to the brain. From this, it is essential to carry out further investigations, so that there is a deeper analysis of this theme.